Case report: A complicated course of Collet-Sicard syndrome after internal carotid artery dissection and lenticulo-striatal artery infarction - Nowak, Dennis A.; Linden, Rainer; Arnold, Peggy; Seitz, Veronika; Stangl, Katrin; Wendl, Christina; Schlachetzki, Felix (Frontiers in Neurology, 2022)
A 40-year-old Caucasian man presented with sudden onset of left-sided hemiparesis associated with dysphonia, dysphagia, and right-sided weakness on shoulder elevation and head rotation. Clinical examination revealed deviation of the tongue to the right, absence of the right-sided gag reflex, right-sided palatal and vocal cord paresis, and weakness of the right trapezius and sternocleidomastoid muscles, all in addition to left-sided brachiocephalic accentuated hemiparesis. Diagnostic examination revealed dissection of the right carotid artery with occlusion of the middle cerebral artery and infarction in the lenticular-striatal artery territory. Mechanical thrombectomy with stent angioplasty of the right internal carotid artery was performed. The paresis of the left side of the body completely regressed within a week after symptom onset, but dysphonia, weakness of the right trapezius and sternocleidomastoid muscles, and especially dysphagia persisted and regressed slowly but gradually. The patient required percutaneous gastric tube feeding for the next twelve weeks, possibly due to involvement of the subcortical white matter tracts. The constellation of symptoms and clinical findings were consistent with Collet-Sicard syndrome, an extremely rare disorder caused by direct compression of the caudal cranial nerves at the base of the skull.